2020
DOI: 10.18517/ijaseit.10.2.9489
|View full text |Cite
|
Sign up to set email alerts
|

Modernizing Dairy Farm: A Production Mode Analysis

Abstract: Appearing livestock modernity due to a greater dependency on the market and actions follows the capitalistic logic of production. This study focuses on the mode of production in developing dairy cattle in the modernity era. Data collection was carried out through observations, recordings, and deep interviews for key informants using the snowball technique. The data were compiled in forms of field notes and audio records transferring into written transcription. Those data were then analyzed using thematic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Modernization and information technology can improve working conditions in agriculture and make the sector more attractive to young people. Research has consistently found that young people are more likely to develop the economy through agriculture, and financial support is crucial to this (Chiswell 2018;Karttunen et al 2016;Widiyanti et al 2018;Yang 2013;St Aisyah et al 2020). As a whole, digitalization has a significant positive impact on generational change in agriculture.…”
Section: Digitalization and Modern Farming Practicesmentioning
confidence: 99%
“…Modernization and information technology can improve working conditions in agriculture and make the sector more attractive to young people. Research has consistently found that young people are more likely to develop the economy through agriculture, and financial support is crucial to this (Chiswell 2018;Karttunen et al 2016;Widiyanti et al 2018;Yang 2013;St Aisyah et al 2020). As a whole, digitalization has a significant positive impact on generational change in agriculture.…”
Section: Digitalization and Modern Farming Practicesmentioning
confidence: 99%
“…New and sophisticated technology requires effort to be adopted by farmers [13]. Many factors affect farmers' adopt new technology.…”
Section: Introductionmentioning
confidence: 99%